Correlation between the Warburg effect and progression of triple-negative breast cancer - Liu, Shaojun; Li, Yuxuan; Yuan, Meng; Song, Qing; Liu, Min (Frontiers in Oncology, 2023)
Triple-negative breast cancer (TNBC) is ineligible for hormonal therapy and Her-2-targeted therapy due to the negative expression of the estrogen receptor, progesterone receptor, and human epidermal growth factor receptor-2. Although targeted therapy and immunotherapy have been shown to attenuate the aggressiveness of TNBC partially, few patients have benefited from them. The conventional treatment for TNBC remains chemotherapy. Chemoresistance, however, impedes therapeutic progress over time, and chemotherapy toxicity increases the burden of cancer on patients. Therefore, introducing more advantageous TNBC treatment options is a necessity. Metabolic reprogramming centered on glucose metabolism is considered a hallmark of tumors. It is described as tumor cells tend to convert glucose to lactate even under normoxic conditions, a phenomenon known as the Warburg effect. Similar to Darwinian evolution, its emergence is attributed to the selective pressures formed by the hypoxic microenvironment of pre-malignant lesions. Of note, the Warburg effect does not disappear with changes in the microenvironment after the formation of malignant tumor phenotypes. Instead, it forms a constitutive expression mediated by mutations or epigenetic modifications, providing a robust selective survival advantage for primary and metastatic lesions. Expanding evidence has demonstrated that the Warburg effect mediates multiple invasive behaviors in TNBC, including proliferation, metastasis, recurrence, immune escape, and multidrug resistance. Moreover, the Warburg effect-targeted therapy has been testified to be feasible in inhibiting TNBC progression. However, not all TNBCs are sensitive to glycolysis inhibitors because TNBC cells flexibly switch their metabolic patterns to cope with different survival pressures, namely metabolic plasticity. Between the Warburg effect-targeted medicines and the actual curative effect, metabolic plasticity creates a divide that must be continuously researched and bridged.